Evaluating the Entrepreneurial Performance in South America. Case of Chile - Gonzalez Flores, Oscar (International Journal of Engineering and Management Sciences, 2024)
The research objective is to explore Chile's entrepreneurial landscape by assessing individual characteristics and institutional factors through a 'pillars' framework and compare it against Colombia, and Brazil; to identify socio-economic, individual, and institutional differences using the Global Entrepreneurship Index (GEI); to apply bottleneck approach to highlight areas requiring policy intervention. GEI features individual and institutional stage variables in a method where every variable collaboratively interacts, incorporating 14 foundational elements and three sub-indexes: attitudes, abilities, and aspirations. Ranking 18th on the GEI globally and the best in Latin America, Chile excels in key entrepreneurial pillars, showcasing strengths in innovation and a robust entrepreneurial culture. Brazil closely rivals Chile in competition and networking, emphasizing political and economic influence. Colombia surpasses Chile in internationalization and growth-stimulating policies but faces challenges like historical conflicts and wealth distribution. This study identified areas where immediate policy intervention may be necessary by examining Chiles's entrepreneurial ecosystem. The Penalty for Bottleneck (PFB) technique identified the weakest pillars highlighting process innovation, competition, and internationalization. The primary component identified as a bottleneck for resource allocation is Process Innovation, accounting for 73% of the allocation, followed by Competition at 23%. The findings show that allocating more resources to process innovation may improve greatly the overall GEI score.